2012
DOI: 10.3109/01612840.2012.665156
|View full text |Cite
|
Sign up to set email alerts
|

Trucking Organization and Mental Health Disorders of Truck Drivers

Abstract: There are over 3 million truck drivers employed in the commercial transportation and material moving occupations, one of the largest occupational groups in the United States. Workers in this large and growing occupational segment are at risk for a range of occupational health-induced conditions, including mental health and psychiatric disorders due to high occupational stress, low access and use of health care, and limited social support. The purpose of this study was to explore male truck drivers' mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 34 publications
5
72
3
4
Order By: Relevance
“…Furthermore, obtained differences in terms of Job Strain between drivers in both clusters (i.e., higher Job Strain rates for participants in cluster number 1) result consistent to other empirical research documenting the critical relationships existing between: a) job stress and both addressed addictive behaviors [34, 78,79], b) job stress and traffic accidents [49,80,81], and c) addictive behaviors such as alcohol consumption, lifestyle factors and safety outcomes [81,82]. It also suggests the need for the development of comprehensive interventions on psychosocial factors at work, keeping in mind the recent growing evidence on the impact of working conditions and its related processes, such as fatigue [83], burnout [52] and social support [84], contributing to the emergence of new risks for health [85], and welfare of professional drivers [86].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, obtained differences in terms of Job Strain between drivers in both clusters (i.e., higher Job Strain rates for participants in cluster number 1) result consistent to other empirical research documenting the critical relationships existing between: a) job stress and both addressed addictive behaviors [34, 78,79], b) job stress and traffic accidents [49,80,81], and c) addictive behaviors such as alcohol consumption, lifestyle factors and safety outcomes [81,82]. It also suggests the need for the development of comprehensive interventions on psychosocial factors at work, keeping in mind the recent growing evidence on the impact of working conditions and its related processes, such as fatigue [83], burnout [52] and social support [84], contributing to the emergence of new risks for health [85], and welfare of professional drivers [86].…”
Section: Resultsmentioning
confidence: 99%
“…20 Shattell et al found that a large proportion of drivers with depression do not seek professional treatment. 21 Bulmash et al also reported that patients with untreated depression displayed significantly slower steering reaction times and experienced a significantly increased number of crashes in a driving simulator compared to those without depression. 22 In Australia, the 12-month prevalence of affective disorders, including depression in adults aged 16 to 85 years is 6.2% overall and 5.3% for males.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is significant from the point of view that majority of the patients were truck drivers by occupation. Truck drivers have been consistently found to be working in difficult conditions and having significantly greater fatigue and mental comorbidity (Sabbagh‐Ehrlich, Friedman, & Richter, ; Shattell, Apostolopoulos, Collins, Sönmez, & Fehrenbacher, ). Understandably, abuse of natural opiates, particularly poppy husk, has been found to be significantly greater among Indian truck drivers (Karia et al, ).…”
Section: Discussionmentioning
confidence: 99%